Peran Bank Wakaf Mikro dalam Meningkatkan Kesejahteraan Masyarakat di Papua: Pendekatan Maqshid Syariah - Putri, Oggy Maulidya Perdana; Marasabessy, Masaalah (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
The establishment of the Micro Waqf Bank offers a viable approach to mitigating poverty and enhancing the quality of life for individuals. The Micro Waqf Bank aims to enhance individuals' quality of life by offering access to sharia-compliant financial services and business support. The objective of this study is to elucidate the function of the Honai Sejahtera Papua Micro Waqf Bank in enhancing customer well-being from the standpoint of Maqashid Syariah. This study employs a descriptive qualitative research design, utilizing primary data collected through interviews and recording. This research involves the process of data analysis, which encompasses data gathering, data reduction, and the derivation of conclusions. The findings of this study demonstrate that the Honai Sejahtera Papua Micro Waqf Bank plays a significant role in achieving the well-being of its customers. The community's ability to uphold religious principles, protect their spiritual health, maintain their reason, ensure the welfare of their offspring, and safeguard their assets serves as proof of this. The findings of this study imply that Micro Waqf Bank as an institution that provides access to sharia-based capital is a form of effort to safeguard assets with utilization that has an impact not only on increasing income but also on improving the fulfillment of basic needs. It proves that the potential of waqf is able to build the ummah's economy. This research implies that Bank Wakaf Mikro Honai Sejahtera could inspire other financial institutions and the Papuan government to adopt Islamic banking models.